New insights on fission of 235U induced by high energy neutrons from a new measurement at n_TOF - A. Manna; E. Pirovano; P. Console Camprini; L. Cosentino; M. Dietz; Q. Ducasse; P. Finocchiaro; C. Le Naour; D. Mancusi; C. Massimi; A. Mengoni; R. Nolte; et al. (Physics Letters B)
The 235U(n, f) reaction cross section was measured relative to neutron-proton elastic scattering for the first time in the energy region from 10 MeV to 440 MeV at the CERN n_TOF facility, extending the upper limit of the only previous measurement in the literature by more than 200 MeV. For neutron energies below 200 MeV, our results agree within one standard deviation with data in literature. Above 200 MeV, the comparison of model calculations to our data indicates the need to introduce a transient time in neutron-induced fission to allow the simultaneous description of (n, f) and (p, f) reactions.